Wings of Wrath: Blake’s Poetics of Revolution and Mythopoiesis - Muñoz García, Adrián (Amaltea. Revista de Mitocrítica, 2011)
This essay explores the dynamics of discursive and symbolic interplay in William Blake’s poetics. By focusing especially on the poem America, the text offers an analysis of the intersecting arena of religious imagery and Blake’s own mythology. Blake’s interest in the American and French revolutions plays an important role in his work, but it was also molded by his distinct view of mankind, itself envisaged through a modified Christian symbolism. Thus, the political upheavals in America and Europe are framed within an Apocalyptic symbolism that, from Blake’s mythic vision, points toward the spiritual renovation of mankind via the attainment of social freedom.